Noise and Environment - Siano, Daniela; Elizabeth González, Alice (IntechOpen, 2021)
Noise pollution is one of the factors that affect the quality of life of the general population, especially in urban areas, where the noise levels are often high due to the presence of numerous sources, such as transport infrastructures, activities production and commercial areas, entertainment venues and other sound sources which, although temporary, such as construction sites and outdoor music events, affect general noise levels. Even if noise is one of the oldest pollutants referred to in history, for years, the problem of noise pollution has been often considered less important than others related to the environment, such as air pollution, water pollution, and waste management.The regulations in force to contain the noise have become increasingly stringent as each individual is constantly exposed to noise and often the noise is treated just as a scourge of modern society. Making noise is becoming easier and cheaper each day, but just the opposite for controlling it. Deeper studies are needed to understand the core of current noise problems; new materials and techniques are needed to control them. This book is a combination of theory and practice based on the latest research. The studies in this book range from evaluation methods for the perception of noise and outline forecast criteria that can be integrated with applications for acoustic mapping as well as the use of innovative techniques and materials for its abatement. The main purpose of this book, organized in 8 chapters, is to provide an overview of the recent studies in this field and the applications in different research studies. The authors, contributing to the success of this book, provide a series of practical applications of their recent studies aimed at the reduction of noise in different environments. The editors would like to thank all the authors who, through their studies and research, have accepted our invitation to share recent discoveries in this field with the scientific community.